Solving a Logic Puzzle via Mathematical Programming - Saltzman, Robert M; Kohler, David (Mathematics and computer education, 2002)
Saltzman and Kohler explore the relative strengths and weaknesses of the spreadsheet approach versus specialized mathematical programming software for solving a particular logic puzzle. The puzzle can be solved manually, in perhaps half an hour or so. However, its formulation in Excel reveals a number of interesting techniques useful for solving other constraint satisfaction and combinatorial problems in this environment.